Analisis Audit Kepatuhan Standar Pelayanan Minuman Angkutan Kereta API Penumpang di Stasiun Besar Medan - Nadia Khairunnisa; Muhammad Arief (Universitas Muhammadiyah Enrekang, 2022)
This research is a qualitative descriptive study that aims to determine or describe the concept of whether the compliance audit consisting of tangible, reliability, responsiveness, assurance, empathy, has been carried out according to the minimum service standards of passenger train transportation at Medan Besar stations or not. The minimum service standard itself is the minimum service size that must be met by service providers in providing services to service users which must be completed as obligations and promises to the community in the context of quality, fast, easy, affordable and measurable services. This study took 3 respondents, consisting of the service division at PT KAI Divre 1 SU, the legal division at PT KAI Divre 1SU, and train passengers. Methods of data collection using interview techniques, observation and documentation. The results of the study indicate that obedience as an operator of railway facilities related to tangible, reliability, responsiveness, assurance, empathy in the implementation of compliance audits of minimum service standards for passenger trains at large stations in Medan to fulfill passenger satisfaction, has been carried out well, although it has not been fully carried out and so on. must be repaired. This can be seen from the level of satisfaction of the passengers who still have findings and complaints.